Daytime Dynamo Electrodynamics With Spiral Currents Driven by Strong Winds Revealed by Vapor Trails and Sounding Rocket Probes. Issue 15 (3rd August 2020) - Pfaff, R.; Larsen, M.; Abe, T.; Habu, H.; Clemmons, J.; Freudenreich, H.; Rowland, D.; Bullett, T.; Yamamoto, M.‐Y.; Watanabe, S.; Kakinami, Y.; Yokoyama, T.; et al.
Abstract: We investigate the forces and atmosphere‐ionosphere coupling that create atmospheric dynamo currents using two rockets launched nearly simultaneously on 4 July 2013 from Wallops Island (USA), during daytime Sq conditions with ΔH of −30 nT. One rocket released a vapor trail observed from an airplane which showed peak velocities of >160 m/s near 108 km and turbulence coincident with strong unstable shear. Electric and magnetic fields and plasma density were measured on a second rocket. The current density peaked near 110 km exhibiting a spiral pattern with altitude that mirrored that of the winds, suggesting the dynamo is driven by tidal forcing. Such stratified currents are obscured in integrated ground measurements. Large electric fields produced a current opposite to that driven by the wind, believed created to minimize the current divergence. Using the observations, we solve the dynamo equation versus altitude, providing a new perspective on the complex nature of the atmospheric dynamo. Plain Language Summary: Two rockets with scientific instruments were launched in the middle of the day to study the upper atmosphere and how it interacts with the ionosphere. The rockets ascended to altitudes of about 140 km—just high enough to gather the necessary data—before coming back down along parabolic trajectories. A vapor trail released by one rocket was photographed on an airplane and showed the upper atmosphere moving at very large speeds, much larger than previously believed. In fact, these winds were so large and changed speed so quickly that in some places the upper atmosphere became turbulent. Instruments on the second rocket gathered information about the ionosphere, including the number of ions present and how the currents and electric fields associated with those charged particles varied with altitude, particularly where the winds were strongest. The winds and currents both displayed a spiral pattern with altitude indicative that they were driven by atmospheric forcing from below. By combining all of these measurements, we are able to better determine what drives the worldwide system of currents at the base of the ionosphere. This "daytime dynamo" is a fundamental part of our natural world, swirling high above us and changing every day. Key Points: Comprehensive observations of the daytime Sq dynamo electrodynamics have been gathered for the first time Observed daytime winds in the dynamo region are much larger than expected yet their currents are reduced by those of DC electric fields Winds and currents exhibit an interleaved spiral pattern indicative of tidal forcing